Alternative reflections on the treatment of violence and crime in Latin America: the prevention of crime as a strategy - Mario Pavel Díaz Román; Othón Partido Lara; María Cecilia Jaramillo Minchel (Social Medicine Publication Group, 2019)
Latin America is the most violent region in the world with a rate of 24.24 homicides per 100,000 inhabitants. In view of this situation, different types of measures have been implemented, ranging from a purely punitive approach to the design and application of programs to prevent violence and crime with various results. On this last point we will reflect, specifically on the relevance and usefulness of such initiatives, besides presenting some key cases in the region for the understanding of the prevention approach; likewise, its scope and limitations will be presented.